Analisis Pengaruh Kualitas Informasi, Kualitas Sistem dan Kualitas Layanan Terhadap Kepuasan Pengguna Pada Aplikasi Tokopedia Dengan Model Delone And Mclean Di Kota Palembang - Ahmad Muharsyah; Rika Kharlina Ekawati (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2021)
The purpose of this study is to prove that the information quality, service quality, and system quality of the Tokopedia application have an influence on the satisfaction of the Tokopedia application users either partially or simultaneously by using the Delone and Mclean method. This model is used to measure the success of information systems and is known as a simple model but is considered quite valid by researchers. The variables measured in this method are taken from the Delone and McLean models which include information quality, system quality and service quality which are tested to see their effect on user satisfaction. The population in this study are the users of the Tokopedia application in the city of Palembang where the number of samples taken is 100 respondents determined by using the Lemeshow formula. The research method used is a survey with a questionnaire which is analyzed using SPSS tools to determine the results of the T test and F test. The results show that partially the quality of information has no effect, but other variables have an influence on user satisfaction. Simultaneously, all variables together have a significant positive effect on user satisfaction.